Promoção da saúde do cuidador familiar de idosos dependentes : uma gerontotecnologia baseada na teoria de Nola Pender - Souza, Camila Aparecida Wagner de (2018)
Introduction: Brazilian population growth is linked to the raise in degenerative chronic diseases. Hence, the creation of strategies to improve the population’s health promotion is needed. One of these strategies is related to health education. Objective: To develop and produce a cell phone application as a piece of gerontotechnology for the dependent elderly family caregiver’s health promotion. Methodology: The Convergent Care Research method was applied. The inclusion criteria were: to be an elderly family caregiver; to be 18 years old or more; to be the main caregiver of a totally or partially dependent elderly person. The exclusion criteria were: To be the caregiver of an independent elderly person; To be a family caregiver that has the aid of a formal or informal caregiver at any period of the day (morning/evening/night). The study was approved by the Research Ethics Committee of the Health Sciences Centre of the Federal University of Espirito Santo, and by the Opinion No. 1.987.228. Results: It is highlighted in the study that most caregivers were female (81.82%); and most were of the age range 51-60 years old (36.36%), and wives (54.55%). It is also highlighted in this study that stress is a reaction of the organism in the face of situations that demand physical and emotional effort to be overcome. The caregivers have previous knowledge related to their own health care, the promotion of health, healthy feeding, among others. However, due to their intense care routine, it isn’t possible for them to organize means for their full own care. Final Considerations: The results of this study have confirmed the need for the creation of projects with the aim at valuing and conducting instruction activities with the caregivers of the elderly, corroborating for their behavioural change. The cell phone application Techcare has enabled the caregivers the opportunity to comprehend their own knowledge about health and about the care of the other, and also to understand about the behaviour changes that are needed for the promotion of their own health.